Ultrahigh β-phase content poly(vinylidene fluoride) with relaxor-like ferroelectricity for high energy density capacitors - Nan Meng (Nature Portfolio, 2019)
Dielectric materials are candidates for electric high power density energy storage applications, but fabrication is challenging. Here the authors report a pressing-and-folding processing of a dielectric with relaxor-like behavior, leading to high energy density in a polymer-based dielectric capacitor.